PEMBUATAN BRIKET DARI KULIT KOPI SEBAGAI BAHAN BAKAR ALTERNATIF RAMAH LINGKUNGAN - Rafidani Elfirdaus; Santoso, Rafi Zahid; Arifin Aji Nugroho; Agus Widayoko (SMA Trensains Muhammadiyah Sragen, 2024)
Fuel is an energy requirement that is needed by society. The increase in population is directly proportional to the consumption of fossil fuels. Therefore, one way to overcome the problem of fossil energy consumption is to develop alternative renewable energy sources. Potential renewable alternative energy is plantation and industrial waste, which currently has not been utilized optimally. Coffee is one of the most important commodities in the national economy. Apart from that, coffee has fans in terms of consumption. The amount of coffee consumed is directly proportional to the increase in coffee skin waste. Coffee skin itself has a high calorific value, so it is very good if processed into briquettes. This research aims to find out how to make briquettes using coffee skin waste. The research method used is a qualitative descriptive method with a focus on making briquettes from coffee skins. The data collection method is carried out by observation. The data that has been obtained is analyzed using descriptive methods. The tests carried out in this research included organoleptic tests, density tests, ash content tests, and combustion rate tests. Based on the tests that have been carried out, this research has succeeded in identifying the effectiveness of coffee husk briquettes as an alternative fuel in the context of utilizing coffee husk waste.